Multi-criteria decision analysis in diabetes mellitus: a systematic literature review - Zakaria, Noor Azura; Said, Abdul Hadi; Ismail, Amelia Ritahani; Tajuddin, Taniza; Huda, Muhammad Qomarul; Suryady, Zeldi (Semarak Ilmu Publishing, 2024)
Decision-making process for diabetes patients is crucial and requires careful attention since it will impact the patient’s safety and overall quality of care. There are many criteria that should be considered by the doctor or healthcare practitioners in making the decisions which make it more difficult for them. Therefore, a standard mechanism should be taken to ensure the consistency of the judgement for diabetes management. Multi-Criteria Decision Analysis (MCDA) is one of the approaches that can be used to produce a precise judgment with multiple factors. The aim of this study is to conduct a Systematic Literature Review (SLR) to examine the MCDA studies in diabetes mellitus domain which until now has been understudied. From 35 studies, further investigations were conducted in terms of the criteria for decision-making process, Multi-Criteria Decision Analysis (MCDA) techniques and evaluation techniques employed in the diabetes mellitus management. This study can be a fundamental reference for researchers, medical doctors and healthcare practitioners in diabetes mellitus management. In addition, researchers in MCDA also can benefit from this study to further improve the technique by incorporating the criteria to ensure that it can assist the decision-making process in diabetes management.